Clinical and genetic spectra of autosomal dominant tubulointerstitial kidney disease. Issue 2 (14th September 2021) - Mabillard, Holly; Sayer, John A; Olinger, Eric
Abstract: Autosomal dominant tubulointerstitial kidney disease (ADTKD) is a clinical entity defined by interstitial fibrosis with tubular damage, bland urinalysis and progressive kidney disease. Mutations in UMOD and MUC1 are the most common causes of ADTKD but other rarer ( REN, SEC61A1 ), atypical ( DNAJB11 ) or heterogeneous ( HNF1B ) subtypes have been described. Raised awareness, as well as the implementation of next-generation sequencing approaches, have led to a sharp increase in reported cases. ADTKD is now believed to be one of the most common monogenic forms of kidney disease and overall it probably accounts for ∼5% of all monogenic causes of chronic kidney disease. Through international efforts and systematic analyses of patient cohorts, critical insights into clinical and genetic spectra of ADTKD, genotype–phenotype correlations as well as innovative diagnostic approaches have been amassed during recent years. In addition, intense research efforts are addressed towards deciphering and rescuing the cellular pathways activated in ADTKD. A better understanding of these diseases and of possible commonalities with more common causes of kidney disease may be relevant to understand and target mechanisms leading to fibrotic kidney disease in general. Here we highlight recent advances in our understanding of the different subtypes of ADTKD with an emphasis on the molecular underpinnings and its clinical presentations.